Gender Equality in English Electronic School Textbook (BSE) for Senior High School (The Case of Interlanguage for Science and Social Study Programme Grade XII) - Dian Safitri (ETERNAL (English Teaching Journal), 2020)
This study is a content analysis which aims at identifying sexist language types which exist in Interlanguage for Science and Social Study Programme Grade XII, revealing how gender roles are communicated as appropriate by the textbook, and how the textbook’s writers reflect gender equality. The result of this study showed that the type of sexist language which exists in the textbook is only “men as standard”. In addition, how this textbook communicates female gender roles as appropriate are by exposing contents which suggest that women cannot use their womb and brain at the same time, women are different from men, women cannot be both feminine and competent at the same time, and women will become less valuable as they age. Concerning men, the contents imply that men are physically strong, men must be successful in holding their professions, men must be the head of his family who have to earn money for the family, men must act independently, and men must be heterosexual and sexually active. Hence, it can be said that the writers of this textbook do not reflect gender equality. Therefore, the way how the writers reflect gender equality was not revealed. Further, the result of this study will be great interest to syllabus designers in composing the content of the textbooks. It is essential for them to take into account the learners’ gender equality in all forms because the instructional objectives of an educational program will not be achieved unless they do so.